1994
DOI: 10.1007/bf01310569
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporin A inhibits vaccinia virus replication in vitro

Abstract: The effect of the immune modulator, Cyclosporin A (CsA) on vaccinia virus replication has been examined in cell cultures. In the present study we report that CsA is anti-viral towards vaccinia virus. Viral yield was inhibited by more than 97% after 24 h postinfection in the presence of 16 microM to 40 microM CsA. An analysis of the infectious cycle in greater detail revealed that CsA did not effect the total level of [35S] methionine incorporation into vaccinia infected cells. However, both early and late vira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 36 publications
4
45
0
Order By: Relevance
“…3N, asterisk) than in untreated cells (Fig. 3K), which is consistent with previous reports that viral DNA replication is inhibited in VVinfected cells treated with CsA (15,16). Under these conditions, virus progeny production was inhibited to a level 87.4% lower than that in untreated VV-infected BSC-40 cells.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…3N, asterisk) than in untreated cells (Fig. 3K), which is consistent with previous reports that viral DNA replication is inhibited in VVinfected cells treated with CsA (15,16). Under these conditions, virus progeny production was inhibited to a level 87.4% lower than that in untreated VV-infected BSC-40 cells.…”
Section: Resultssupporting
confidence: 81%
“…2). The immunosuppressant CsA was reported to severely inhibit VV progeny production (15), and this effect was correlated with its ability to bind CypA (16). Therefore, we were most interested in investigating the effect of CsA on CypA rearrangement during infection.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…30 Regarding human immunodeficiency virus type I, in particular, it was suggested that CsA suppresses viral infection through inhibition of the function of CyP, which plays an important role in the life cycle of human immunodeficiency virus type I. 31 The precise molecular mechanism of anti-HCV activity of CsA remains to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…The antiviral activity and mechanism of action of CsA was first described for HIV 152 and for VV 153 . CsA inhibits cellular cyclophilins that interact with HIV Gag polyproteins 152 and late proteins of VV 154 , thereby facilitating their correct folding and assembly of replication complexes.…”
Section: Bsas Derived From Fungi: Cyclosporine Statins and Mycophenomentioning
confidence: 99%